Golda Meir Israel's matriarch - Lipstadt, Deborah E. 1947- (Yale University Press, 2023)
A balanced biography of Golda Meir, who was both adored and abhorred, from award-winning author Deborah E. Lipstadt "Comprehensive. . . . Always thoughtful. . . . A nuanced account of a leader whose influence endures in the Middle East."-Kirkus Review Golda Meir (1898-1978) was the first and only woman to serve as prime minister of Israel. She was born in Kiev into a childhood of poverty, hunger, and antisemitism. When she was five, her father left to find work in America, and a year later the family settled in Milwaukee, Wisconsin. As a teenager she became devoted to Labor Zionism, giving street-corner speeches, and her family's home became a destination for Zionist emissaries. Her love for Labor Zionism was so fervent that her boyfriend, Morris Meyerson (her future husband), was often in competition with her dedication to the cause. Zionism prevailed. In 1921, Golda left America for Palestine with Morris and her sister Sheyna. Though the reality of living in Palestine was far from the dream of Zionism, Meir settled on the kibbutz Merhavia and was swiftly appointed to the Histadrut (the General Organization of Hebrew Workers in Palestine). As an ally of the Zionist David Ben-Gurion, Meir played an important role in the Yishuv, the pre-state Jewish community in Palestine; proved an almost singular ability to connect and fundraise with diaspora Jewry, particularly Americans; and served in three pivotal positions following Israel's independence: labor secretary of the newly formed state, foreign minister, and Israel's fourth prime minister. In tracing the life of Golda Meir, acclaimed author Deborah E. Lipstadt explores the history of the Yishuv and Jewish state from the 1920s through the 1973 Yom Kippur War, all while highlighting the contradictions and complexities of a person who was only the third woman to serve as a head of state in the twentieth century
Keywords: Prime ministers / Israel / Biography; Women prime ministers / Israel / Biography; Zionists / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; Biografie